Weed management with Triafamone herbicide in transplanted rice ecosystem - Arthanari, P. Murali (Emirates Journal of Food and Agriculture, 2023)
Field experiments were conducted during Rabi 2018-19 (September to January) and Kharif 2019 (May to September). Medium duration rice cv. CO(R) 51 was used as a test variety at Tamil Nadu Agricultural University, Coimbatore, India to study the effect of Triafamone on broad spectrum weed control in transplanted rice. Triafamone was applied at two times. First set of treatments (30, 40,50 and 100 g/ha) applied two to three leaf stage of weeds and second set treatments imposed (30, 40,50 and 100 g/ha) at three days after transplanting of the rice crop. These treatments were compared with Pyrazosulfuron ethy 10% WP @ 15 g/ha, Pretilachlor 5% EC @ 750 g/ha, hand weeding @ 20 and 40 days after transplanting and unweeded control. The major grasses were Echinochloa crus-galli (L.) and E. colonum (L.) while the sedge weed included Cyperus nutans (L.). Among the broad leaved weeds Eclipta alba (L.) and Bergia ammanioides were the dominant species. In both the seasons of the study, lesser population of grass was recorded with the pre and early post emergence application of triafamone herbicide 40 g a.i. ha-1 (1.41 and 1.41 per m-2 at 28 and 42 DAA for both the seasons respectively) and it was closely followed by application of triafamone herbicide 50 g a.i. ha-1 and application of PE Pretilachlor at 0.75 kg a.i. ha-1 and EPOE Pyrazosulfuron ethyl at 15 g a.i. ha-1. The same trend was observed for broad leaved weeds and their weed dry weights. Application of triafamone herbicide at 40 g a.i. ha-1 as pre emergence and early post emergence application recorded highest weed control efficiency of 100, 97.7 and 99.6 % and 97.8% at 42 DAA during both years of experimentation and also resulted in higher grain yield (8052 and 8182 kg ha-1 during rabi 2018-19 and 9018, 9175 kg ha-1 during Kharif 2019). Further, it is noticed that, there was no residual toxicity of herbicide to the succeeding crops. Hence, application of Triafamone 40 g a.i. ha-1 either pre or early post emergence herbicide has higher productivity and no residues in transplanted rice ecosystem. Key words: Triafamone, efficacy, weeds and transplanted rice ecosystem